Comparison of the change in QuantiFERON-TB Gold Plus and QuantiFERON-TB Gold In-Tube results after preventive therapy for latent tuberculosis infection. - Ock-Hwa Kim; Kyung-Wook Jo; Shinhee Park; Yong-Ha Jo; Mi-Na Kim; Heungsup Sung; Tae Sun Shim (PLoS ONE, 2020)
Background We investigated changes in the interferon-γ levels before and after treatment of latent tuberculosis infection (LTBI) using QuantiFERON-TB Gold Plus (QFT-Plus) and QuantiFERON-TB Gold In-Tube (QFT-GIT) assays. The objective was to assess whether QFT-Plus could serve as a biomarker of LTBI treatment response. Methods We prospectively enrolled 44 individuals whose baseline QFT-GIT and QFT-Plus showed positive results at a tertiary referral center in South Korea between March 2017 and March 2018. The results of the QFT-Plus assay were defined as positive if either or both of the antigen tubes (TB1 and/or TB2) were positive. After LTBI treatment, both tests were repeated. Results The mean age of the participants was 47.6 years. The QFT-GIT and QFT-Plus assays revealed positive results in 42/44 (95.5%) and 41/44 (93.2%) participants after LTBI treatment, showing overall agreement of 93.2%, with a Cohen's kappa value of 0.37 (fair agreement). The differences between pre- and post-LTBI treatment interferon-γ levels were measured using the QFT-GIT and QFT-Plus assays. No significant differences were noted among the 3 values: the median difference in interferon-γ value with QFT-GIT, QFT-Plus TB1, and QFT-Plus TB2 was 0.211 IU/mL (IQR, -0.337-3.347), 0.025 IU/mL (IQR, -0.338-1.368), and 0.180 IU/mL (IQR, -0.490-2.278), respectively (P = 0.401). Conclusion The change in interferon-γ levels before and after LTBI treatment measured using the QFT-Plus assay showed a similar trend to that of the QFT-GIT assay. Considering that the QFT-GIT assay is not a useful biomarker of LTBI treatment response, QFT-Plus also appears not to be useful for this purpose.